2017
DOI: 10.1039/c7an01075c
|View full text |Cite
|
Sign up to set email alerts
|

Instant on-paper protein digestion during blood spot sampling

Abstract: A concept integrating sampling and protein digestion is introduced here combining fast and simple fabrication by wax printing on filter paper with trypsin immobilized polymer beads. The paper reactors showed promising results with a high degree of protein digestion within fifty minutes in model protein mixtures as well as in human blood. The model protein mixture was used for the evaluation of performance both with and without a reduction and alkylation step. The paper reactors without reduction and alkylation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

8
0

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 194 publications
(259 reference statements)
2
18
0
Order By: Relevance
“…The latter does not out rule the possibility of good accessibility when few disulfide bonds are present, however, on the other hand, it is not given that the absence of disulfide bonds results in good protein coverages for on-paper digests. In accordance with previously published results [45]. This is probably dependent on additional protein properties.…”
Section: Shotgun Proteomics On-paper Vs In-solutionsupporting
confidence: 93%
See 1 more Smart Citation
“…The latter does not out rule the possibility of good accessibility when few disulfide bonds are present, however, on the other hand, it is not given that the absence of disulfide bonds results in good protein coverages for on-paper digests. In accordance with previously published results [45]. This is probably dependent on additional protein properties.…”
Section: Shotgun Proteomics On-paper Vs In-solutionsupporting
confidence: 93%
“…Our group has been working with the concept of smart sampling in combination with MS determination since 2017 [45]. This concept is based on the covalent binding of trypsin to cellulose allowing a DBS sampler to start with the digestion step at the moment of sampling [46][47][48][49].…”
Section: Introductionmentioning
confidence: 99%
“…This is also seen in the number of high-confidence peptides qualified. As in earlier studies [35], it is seen that carboxymethylated tryptic peptides are found in expected amounts [40]. The latter is of interest since the reduction and alkylation take place after the digestion.…”
Section: Disc Performance On Complex Biological Samplessupporting
confidence: 78%
“…The long-term goal of our research is to simplify MS-based protein analysis from dried matrix samples (such as DBS), and we aim to integrate time-consuming procedures within the sampling device for a prompt start to the sample preparation upon sample collection [29,[35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…One reason for a too low digestion output may be the lack of a reduction and alkylation step prior to digestion. 33 As a simple precautionary measure, initially this step was left out to avoid introduction of the DTT and IAA into the mass spectrometer during direct injection MAI-MS using the syringe method. However, to…”
Section: Mai-srm-ms Of Digested Proteinsmentioning
confidence: 99%